Fault-current predetermination using time- limited CT secondary side measurements by the covariance-Prony method - Kamel, N.; Sankaran, P.; Venkatesh, B. (2004)
Protective current transformers (CTs) are integrated into electrical power systems for assessment of the health of the system. They are intended to provide a scaled-down value of the line current. During major faults, excessive fault currents with decaying DC components could flow through the primary of the CT, causing core saturation and a consequent malfunction of the protection system. This problem is addressed in the paper, and a signal-processing scheme is proposed for fast predetermination of the peak value of the steady-state AC component, instant of occurrence of fault and the time constant of the decaying direct current. Samples of the CT secondary current are collected until the onset of saturation, and are operated upon using a covariance-Prony algorithm to estimate the aforementioned critical parameters. Simulation results in support of the proposed technique are also presented.